Studies on Parabolic Solar Dish Collector – Review - Nishant Kumar Singh (Journal of Advanced Mechanical Sciences, 2022)
A parabolic solar dish collector (PSDC) is like the dish antenna,but it does possess a reflector such as a mirror it contains an absorber at its focal point. It is concentrating solar radiation irradiated over it using that. It tracks the sun everywhere in the sky and gets irradiated with its radiation,for that, it requires powerful computers and dual-axis trackers. This review studies the improvement in hydrothermal efficiency of PDSC using oil-based nanofluids. It also observed that the use of PCM with PDSC may reduce cooking time by 25% and when used in place of a boiler in a small-scale steam power plant, it may reach an overall efficiency of 35%.